The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2309499018770914
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive modified Camitz opponensplasty for severe carpal tunnel syndrome

Abstract: Purpose: We aimed to compare the clinical results and the complications between the minimally invasive modified Camitz opponensplasty and the conventional Camitz opponensplasty for severe carpal tunnel syndrome (CTS), and to evaluate the efficacy of the modified technique for CTS. Methods: Twenty-eight hands in 24 patients with severe CTS who had disorder of the thumb opposition with thenar muscle atrophy (group 1) were treated by minimally invasive modified Camitz opponensplasty, passing the transferred palma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In our study, such atrophy was observed in 49% of patients with CCTS before surgery. However, studies on CCTS have clearly shown that atrophy of the APB muscle in particular is very common [ 33 , 34 ]. Moreover, because of this, many patients lose the ability to oppose their thumb, an activity which is essential for daily functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, such atrophy was observed in 49% of patients with CCTS before surgery. However, studies on CCTS have clearly shown that atrophy of the APB muscle in particular is very common [ 33 , 34 ]. Moreover, because of this, many patients lose the ability to oppose their thumb, an activity which is essential for daily functioning.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement was statistically significant in women; however, no such improvement was observed in the male group. Studies on the electrophysiological measurements of the APB have also indicated improved parameters after surgery [ 34 ]. Capasso’s work on severe CTS demonstrated that the strength of the hand improved after surgery [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional Camitz opponensplasty has several disadvantages. Firstly, the extended incision in the palm and wrist involves extensive soft tissue dissection, which increases the risk of iatrogenic injury to the palmar cutaneous branch of the median nerve 2,7,8 and can cause painful scarring of the wrist 5,9 . Prominent bowstringing of the transferred tendon is one of the main shortcomings 4,8 .…”
Section: Discussionmentioning
confidence: 99%